The theory and practice of professional footcare: experience of a study trip - Bűdi, Károly (Animal welfare, Ethology and Housing Systems (AWETH), 2008)
The author is a 5-year agricultural engineer student at the Szent István University in Gödöllő. During his studies he had the chance to get to know the practice of cows’ footcare on small as well as big farms in Hungary and abroad, too. From November to December in 2006 he participated in a professional grand, in Austria, where he could learn the Austrian practice of footcare. In present article he compares the Hungarian method to Austrian based on his experience.